Penerimaan Santri terhadap Gaya Dakwah Ustadz Abdul Somad: Studi di Pesantren Ibnu Syam 2 Cilegon - Muhammad Ahlun firdaus (STIKes Ibnu Sina Ajibarang, 2025)
Da'wah plays a crucial role in shaping religious understanding and practice among Muslims. Ustadz Abdul Somad is known as one of the da'wah preachers with a unique da'wah approach, combining strong rhetoric, fresh humor, and argumentation based on evidence. This study aims to examine how students at the Ibnu Syam 2 Cilegon Islamic Boarding School respond to and accept the da'wah style delivered by Ustadz Abdul Somad. Using a descriptive qualitative method. The research findings reveal that students generally accept and appreciate Ustadz Abdul Somad's da'wah style for several main reasons: (1) Clear and communicative delivery, so that the material is easier to understand and attracts attention; (2) The use of humor and inspirational stories, which help improve memory of the da'wah message; and (3) The depth of the evidence used, which enriches the students' Islamic insight. In addition, this study shows that students feel more motivated to deepen their understanding of religion and apply Islamic teachings in their daily lives after attending his lecture. This study contributes to understanding the effectiveness of da'wah strategies in Islamic boarding schools and offers insight for preachers regarding more interesting and effective communication approaches. The results of the study also confirm that an interactive, contextual da'wah style that contains intellectual and emotional aspects can increase students' understanding and interest in Islamic teachings.